Review: Anti-Semitism and Schooling under the Third Reich - White, Joseph Robert (Holocaust and genocide studies, 2004)
Anti-Semitism and Schooling under the Third Reich Gregory Paul Wegner New York and London RoutledgeFalmer 2002 xiv + 262 cloth $ 129.95 pbk. $ 26.95 , 1Prince George's Community College